Peculiarities of financial stability of construction enterprises - Loktionova, Ya. F.; Gavrilyuk, V. Ya. (Ліра-К, 2022)
These features also affect indicators and features of the development of the construction sector, one of the most important of which is financial stability.
Keywords: peculiarities of financial stability; construction enterprises